Mobile phone based SCADA systems - Juru, Commerce (Midlands State University, 2019)
Monitoring is very important in Industrial Automation to bring out reliability and accuracy thus the use of a SCADA system. SCADA is an acronym for “Supervisory Control and Data Acquisition.” This systems are widely used in industry for supervisory control and data acquisition of industrial processes. A Android-enabled mobile phone can be used as a client in a SCADA application in order to display and supervise an industrial refrigeration system. The project presents an actual implementation of the on-line controlling of the refrigeration system via mobile phone. The wireless communication between the mobile phone and the SCADA server is performed via a 3G Cloud Router. The operator can visualize and modify the plant parameters using his mobile phone, without reaching the site. In this way maintenance costs are reduced and productivity is increased.